Religious Moderation of Islamic Religious Education Teacher in Pekanbaru City Against Minority of Islamic Mazhab - Zulfadli Achmad; Munawar Rahmat; Aceng Kosasih (AL-ISHLAH: Jurnal Pendidikan, 2023)
The research aims to determine the religious moderation of Islamic religious education (PAI) teachers towards minority Islamic schools of thought. Quantitative research methods, data collection techniques with questionnaires, and data analysis are descriptive-analytic with percentages (%). Three aspects are examined: views on majority Muslims, Shia Islam, and Ahmadiyya, each netted with seven items (total of 21 items). All items have high validity (minimum alpha 0.05) and high reliability (r = 0.94 significant at alpha 0.01). Respondents to the study were 78 high school PAI teachers in the city of Pekanbaru. The study's results showed that most of the Pekanbaru PAI teachers failed to maintain Islamic moderation. They also failed to become preservers of Sunni Islam, which is moderate towards Shia and Ahmadiyya. If this attitude also occurs among Islamic Religious Education teachers in other areas, it is only natural that most students and university students are intolerant of Muslim minorities. Researchers recommend looking for learning models to eliminate negative prejudices and develop religious moderation among Muslims from different schools of thought.